Seismic Ground Motion Amplifications Estimated by Means of Spectral Ratio Techniques: Examples for Different Geological and Morphological Settings - Massa, M.; Lovati, S.; Marzorati, S.; Augliera, P. (IntechOpen, 2011)
None